The forgotten majority : German merchants in London, naturalization, and global trade, 1660-1815 - Schulte Beerbühl, Margrit; Klohr, Cynthia (New York : Berghahn Books, 2015)
The ""forgotten majority"" of German merchants in London between the end of the Hanseatic League and the end of the Napoleonic Wars became the largest mercantile Christian immigrant group in the eighteenth century. Using previously neglected and little used evidence, this book assesses the causes of their migration, the establishment of their businesses in the capital, and the global reach of the enterprises. As the acquisition of British nationality was the admission ticket to Britain's commercial empire, it investigates the commercial function of British naturalization policy in the early m
Sources and outline -- Ch. 1. Naturalizing newcomers for prosperity (1660-1818) -- Early modern English naturalization law -- Naturalized subjects : their number and native lands -- The occupations of German immigrants to become English subjects -- Ch. 2. Promoting Anglo-German trade in the seventeenth century -- Reorganizing Anglo-German trade during the 1600s -- London's German merchants after 1660 -- Lack of trust and understanding : challenges for both sides -- German merchant trade in London -- Trading regions and commodities -- Late-seventeenth-century German trade networks -- German merchants and London trade companies -- Fighting regulated companies -- Politics and commerce -- Ch. 3. Eighteenth-century German houses and trade -- London's German trade houses -- Starting out in London : the way to independence -- Trade houses and partners -- Chain migration, successors, and transnational alliances -- A German perspective on the development of bilateral trade -- The rise and organization of early "merchant empires" -- Connecting colonial empires -- Early merchant empires : flexible and vulnerable -- Ch. 4. German merchants in the Levant and Russia Companies -- British trade with Russia and the Levant -- Naturalized merchants in the Levant Company -- Naturalized merchants in the Russia Company -- The Russia Company's struggle with naturalization practices -- Naturalized subjects and the British factory in St. Petersburg -- The Bank of Scotland's right to naturalize -- Ch. 5. Boom and bankruptcy -- Insurance and trade at London's German trade houses -- London's early insurance business -- Networking Europe with the Americas and Asia -- The bankruptcy trend and the naturalized subjects' bankruptcies -- Waves of bankruptcy during the Coalition Wars -- The size of failed trade houses during the era of the Coalition Wars -- Muilman & Nantes -- Theophilus Blanckenhagen -- Persent & Bodecker -- Oom, Hoolboom, Knoblock & Co. and Hippius & Co. -- Estates of the failed -- Certificate of conformity and the ware broker : starting all over -- Commodity brokers and the freedom of the city -- Conclusion.
English
German-language edition entitled Deutsche Kaufleute in London : Welthandel und Einbürgerung (1660-1818); published by Oldenbourg Wissenschaftsverlag GmbH, München, 2007.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Merchants -- England -- London -- History; Germans -- England -- London -- History; Naturalization -- Great Britain -- History; International trade -- History; Germany -- Commerce -- Great Britain -- History; Great Britain -- Commerce -- Germany -- History; London (England) -- Economic conditions; London (England) -- Ethnic relations -- History